Association between urinary metals and prostate-specific antigen in aging population with depression: a cross-sectional study - Ren, Liquan; Zhang, Yue; Wu, Jinyi (Frontiers in Public Health, 2024)
Objective This study aims to investigate the impact of depression and urinary metals on Prostate-Specific Antigen (PSA).Analysis was conducted on 1901 samples collected from the National Health and Nutrition Examination Survey (NHANES) database between 2001 and 2010.Analytical methods included stepwise multiple linear regression (MLR) analysis of the overall population's urinary metals and PSA relationship, analysis of urinary metals and PSA relationship in elderly and BMI subgroups, analysis of urinary metals and PSA relationship in the depressed population, and restricted cubic spline (RCS) analysis. A significance level of P < 0.05 was considered statistically significant.In the stepwise multiple linear regression, beryllium (Be) showed a dose-response association with PSA (third quartile: β = 0.05, 95%CI (0.02, 0.09); fourth quartile: β = 0.07, 95%CI (0.02, 0.12), p trend = 0.048). Subgroup analysis indicated that in individuals aged >60, Be at Q4 level (β = 0.09, 95%CI (0.05, 0.21)) exhibited a dose-response correlation with PSA. In the population with 25 ≤ BMI < 30, Be might more significantly elevate PSA, with Q4 level having a pronounced impact on PSA levels (β = 0.03, 95%CI (0.02, 1.27)). In the depressed population, urinary cadmium (Cd) levels showed a significant positive dose-response relationship, with Q4 level of Cd having the maximum impact on PSA (β = 0.3, 95%CI (0.09, 0.49)).Individuals exposed to beryllium (Be), especially the elderly and overweight, should monitor their PSA levels. In depressed patients, cadmium (Cd) levels may further elevate PSA levels, necessitating increased monitoring of PSA levels among males.